1978
DOI: 10.1139/f78-212
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Flushing: Effectiveness and Influence on Survival and Condition of Juvenile Salmonids

Abstract: Hydraulic stomach flushing was an effective method to analyze relative food consumption and feeding habits of young salmonids. Coho salmon (Oncorhynchus kisutch) stomachs were most effectively flushed — 99% of invertebrate organisms (96% of weight of stomach contents); 92% of organisms (83% of weight) were flushed from cutthroat trout (Salmo clarki) stomachs, 90% of organisms (77% of weight) were flushed from rainbow trout (S. gairdneri) stomachs. Stomach flushing did not affect survival of juvenile coho salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 4 publications
3
75
1
Order By: Relevance
“…Gastric lavage has been reported to be 99% effective at removing prey organisms, with no impacts on survival, from the stomachs of coho salmon (Meehan and Miller 1978). At each site each sampling trip, the contents from the digestive tracts of up to 20 each of Chinook, coho, and chum salmon (Oncorhynchus keta) were flushed into individual polyethylene sample bottles using filtered river water at ambient temperature.…”
Section: Dietsmentioning
confidence: 99%
“…Gastric lavage has been reported to be 99% effective at removing prey organisms, with no impacts on survival, from the stomachs of coho salmon (Meehan and Miller 1978). At each site each sampling trip, the contents from the digestive tracts of up to 20 each of Chinook, coho, and chum salmon (Oncorhynchus keta) were flushed into individual polyethylene sample bottles using filtered river water at ambient temperature.…”
Section: Dietsmentioning
confidence: 99%
“…In contrast, Harleb and Moring (1995) documented that stomach flushing caused 60% mortality in golden shiners. Meehan and Miller (1978) found that stomach flushing caused reduced condition in hatcheryreared juvenile coho salmon, but not in wild salmon. The current literature on hooking mortality and tournament-associated mortality documents a strong positive relation between handling-induced mortality and water temperature (e.g., Muoneke and Childress, 1994;Wilde, 1998).…”
Section: Recommendationsmentioning
confidence: 94%
“…Syringes have also been used to directly inject water into the stomach of fish through the mouth and esophagus (Aho, 1976;Meehan and Miller, 1978). When the water was forced into the stomach, the stomach contents were flushed back through the esophagus and mouth, through a funnel into a collecting jar.…”
Section: Syringesmentioning
confidence: 99%
See 1 more Smart Citation
“…The gastric lavage (GL) method using a syringe to inject water through the mouth and oesophagus is the most promising one for small sized species (Meehan and Miller 1978, Hyslop 1980, Kamler and Pope 2001. However, many risks that may be associated with this method were not properly considered and/or tested, such as stress, prolonged handling time, tissue damage in the oesophagus and stomach (Shuman and Peters 2007), as well as survival and longevity after release back into the natural environment.…”
mentioning
confidence: 99%